Handling the Impact of Flood Disaster Risk in Pontang Village, Ambulu District, Jember Regency: Penanganan Dampak Risiko Bencana Banjir Pada Desa Pontang Kecamatan Ambulu Kabupaten Jember - Wicaksono, Galih; Rendy Setiawan; Krisnamurti; Anik Suwandari; Luh Putu Indah Budyawati (Yayasan Ahmar Cendekia Indonesia, 2023)
Flooding is one of the disasters experienced by several areas in Jember Regency, especially in Ambulu District, one of which is Pontang Village. Although residents do not consider flooding as a threat because the intensity of flood events is still relatively low. However, if it is not anticipated, it will of course disrupt the activities of village communities. The aim of this activity is to provide knowledge and skills in handling the impact of flood risk to village communities and especially to the Pontang Disaster Response Village (Destana) team. This activity consists of various activities such as grants for main and supporting equipment, training and outreach, as well as activity evaluation. The result of this activity was an increase in the knowledge and skills of the village community and the Destana Pontang team regarding flood management and techniques for using the main and supporting equipment that was donated. Participants were also enthusiastic about taking part in activities organized by the implementing team, so it is hoped that this activity can be of added value for the village community and the Destana Pontang team in facing disasters in the future.Key words: Disaster Response Village, Flood AbstrakBanjir merupakan salah satu bencana yang dialami oleh beberapa wilayah di Kabupaten Jember, khususnya di Kecamatan Ambulu, yang salah satunya di Desa Pontang. Meskipun warga masyarakat tidak menganggap banjir sebagai ancaman karena kejadian banjir intensitasnya masih relatif rendah. Namun demikian apabila tidak diantisipasi, tentu saja akan mengganggu aktifitas masyarakat desa. Tujuan kegiatan ini adalah untuk memberikan pengetahuan dan keterampilan penanganan dampak risiko banjir kepada masyarakat desa dan khususnya kepada tim Desa Tanggap Bencana (Destana) Pontang. Kegiatan ini terdiri dari berbagai aktifitas seperti hibah peralatan utama dan pendukung, pelatihan dan sosialisasi, serta evaluasi kegiatan. Hasil kegiatan ini adalah adanya peningkatan pengetahuan dan keterampilan masyarakat desa dan tim Destana Pontang terkait penanganan banjir dan teknik penggunaan peralatan utama dan pendukung yang dihibahkan. Peserta juga antusias dalam mengikuti kegiatan yang diselenggarakan tim pelaksana, sehingga diharapkan kegiatan ini dapat menjadi nilai tambah bagi masyarakat desa dan tim Destana Pontang dalam menghadapi bencana dimasa mendatang.